UTILIZATION OF PARTICIPATORY COMMUNICATION FOR SUSTAINABLE FOOD SECURITY IN EAST LAMPUNG DISTRICT - Hanindyalaila Pienrasmi; M. Fikri Akbar; Sandy Allifiansyah (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Food security is an important pillar in sustainable development, especially in rural areas that are the center of food production. East Lampung Regency, as one of the agricultural centers in Indonesia, faces challenges in realizing food security that is not only sufficient in quantity, but also sustainable in the long term. This study aims to examine how the use of participatory communication can support the strengthening of food security through the empowerment of farmer communities. The focus of the study is directed at the communication process that occurs in the implementation of the Community Food Distribution Institution Strengthening Program. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews with a combination of farmer groups, member farmers, agricultural extension workers, and direct observation of food deliberation and distribution activities. Data were analyzed using thematic analysis techniques to find communication patterns, levels of participation, and their impact on increasing community capacity and independence. The results of the study show that participatory communication can build trust, encourage active farmer involvement, and strengthen the function of food institutions at the local level. Group discussions, open deliberations, and intensive interpersonal communication between the administrators of farmer groups and members are key to facilitating the process of food distribution and storage of food reserves. In addition, the use of easy-to-understand language and the suitability of communication media to the local context are supporting factors for successful communication. This study confirms that the participatory communication approach is not only a means of conveying information, but also a transformative strategy for building critical awareness and active participation in realizing sustainable food security in rural areas.